PELATIHAN SOLIDWORKS 3D CAD BAGI SISWA SEKOLAH MENENGAH KEJURUAN DI DESA CIANTRA - Bayu Candra Pradana; Fatimah Dian Ekawati (Universitas Islam 45 Bekasi, 2022)
The aim of this program is to develop the potential of students in the field of design before entering the industrial world. As time goes by, technology advances rapidly, the manufacturing industry continues to attract jobs along with increasing investment. In this case, it requires competent human resources. This activity can increase students' understanding and skills before entering the world of work later. The program that has been implemented is Solidworks 3D CAD training through zoom meetings. This training was given to Vocational High School students in the Ciantra village environment for three meetings on 20, 26 and 27 February 2022. The method used is a demonstration, participants follow the tutorial material from the teacher step by step. Prior to the implementation of the activity, participants were given an introduction to Solidworks module to make it easier for students to understand. The training materials include an explanation of the Solidworks toolbar, the creation of two-dimensional (2D) drawings and the creation of three-dimensional (3D) parts. The results of the training can increase students' knowledge in drawing techniques using Solidworks software. In addition, it can improve students' skills in designing workpieces. It is hoped that by improving the skills of these students it will become capital before entering the industrial world.